AB0006 HYPOMETHYLATION OF THE PROMOTER REGION OF TLR4 GENE AT A SYSTEMIC LEVEL IN PATIENTS WITH RHEUMATOID ARTHRITIS AND PERIODONTITIS. (2nd June 2020) - Chatterjee, S.; Bhattacharjee, D.; Misra, S.; Rao, A.; Chattopadhyay, A.; Ghosh, A.
Abstract : Background: Periodontitis (PD) has long been linked with Rheumatoid arthritis (RA) [1]. Epigenetic modifications are being recently explored to explain such associations, DNA methylation being one such important mechanism. Objectives: To study the effect chronic generalized periodontitis on systemic methylation of TLR4 genes in comparison to only RA and RA with PD patients. Methods: Twenty-three RA patients, among which 11 patients had chronic generalized PD, 20 patients with only PD and 15 healthy individuals recruited. DNA was isolated from PBMCs of the participants blood, then were first bisulphite converted and then methylation specific PCR were performed using primers for methylated and um-methylated promoters of TLR4. The DNA amplifications were checked in horizontal gel electrophoresis. The methylation signatures were verified by DNA sequencing (Sanger) of the amplified products. Results: The anti-CCP, DAS-CRP and HAQ DI were higher in patients with both RA and PD (220±40, 5.7±0.2, 1.5±0.1 respectively, p<0.05). Control samples had shown amplification bands for methylated primers of TLR4 but not for un-methylated primers of TLR4. However, only RA, only PD and RA with PD samples, had shown amplification for un-methylated primers and not for methylated primers. These results together with DNA sequencing indicated that 4 CpG sites in the promoter ofTLR4 genes were hypo-methylated in the PBMCs of patients whereas those remain methylated in healthy individuals. Conclusion: The observations indicated that though PD is a localised disease of the gingiva there is a systemic involvement of TLR mediated pathways in them which is similar to those in RA. However, further validation in larger cohort and down-stream signalling molecules needs to be studied. References: [1]Ceccarelli F, Saccucci M, Di Carlo G, Lucchetti R, Pilloni A, Pranno N, Luzzi V, Valesini G, Polimeni A. Periodontitis and rheumatoid arthritis: the same inflammatory mediators?. Mediators of inflammation. 2019;2019. Disclosure of Interests: None declared